Development of fluorescent epoxy composite with carbon-based nanomaterial additives derived from agricultural waste - Tewari, Chetna; Kim, Yebom; Kim, Young Nam; Ryu, Sooyeon; Jeong, Hyun Sung; Jung, Yong Chae (John Wiley & Sons Inc., 2024)
Fluorescent polymers have exciting applications in sensing, imaging, and probes. Agricultural waste is increasingly being used to develop fluorescent nanomaterials due to technology, cost, and waste management advantages. This study developed fluorescent carbon-based nanomaterials, that is, potassium doped graphene oxide (K-GO) from Quercus ilex waste and used them to optimize fluorescent epoxy nanocomposites. The resulting nanocomposites showed significant enhancement in tensile strength with only 0.05？wt% of the renewable nanomaterial. The developed fluorescent epoxy nanocomposites have enhanced thermal and mechanical properties and can be used in sensing, imaging, and other applications.